SEJARAH ISLAM DI NUSANTARA : TELAAH TEORI MASUKNYA, PROSES PENYEBARAN DAN NILAI KONTEKSTUAL - M Farel; Nurzena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study discusses the history of Islam in the Indonesian archipelago, including the theories of its arrival, the process of its spread, and the contextual values that developed in society. This research used a qualitative method with a historical approach through library research. The results show that the arrival of Islam in the archipelago is explained through three main theories, namely the Gujarat, Arab, and Persian theories. The spread of Islam occurred peacefully through trade, marriage, education, Sufism, and political power. In addition, Islam in the archipelago developed values such as tolerance, cultural acculturation, and peaceful dakwah. These values shaped the distinctive and moderate character of Islam in the region.